2020
DOI: 10.13005/msri/170105
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Current Mechanical and Electronic Design Aspects and Future Prospects of Smart Canes for Individuals with Lower Limb Difficulties

Abstract: Smart canes are one of the mobility assistive devices to facilitate the freedom of movement and help people with mobility problems to move around and perform daily chores, which are not possible usually. But they are available in different design options to offer specific advantages. In this review paper, we have addressed different mechanical and electronic designs of assistive devices proposed and developed by various researchers. The aim of our study was to sort out different mechanisms of actions used by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In other words, the auditory signal acted as a feedback signal to correct the subject’s dependence on the cane. An appropriate physical response to the provided feedback improves the function of the somatosensory system of patients with stroke, which helps to control the center of mass and contributes to improvement of gait function [ 23 ]. Sungkarat et al reported that auditory feedback through a pressure sensor applied to the insole shoe wedge during gait training of patients with stroke was effective in improving the weight transfer ability and activating the muscles of the affected lower limb [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the auditory signal acted as a feedback signal to correct the subject’s dependence on the cane. An appropriate physical response to the provided feedback improves the function of the somatosensory system of patients with stroke, which helps to control the center of mass and contributes to improvement of gait function [ 23 ]. Sungkarat et al reported that auditory feedback through a pressure sensor applied to the insole shoe wedge during gait training of patients with stroke was effective in improving the weight transfer ability and activating the muscles of the affected lower limb [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical practice, it is difficult to quantitatively monitor the weight carried on the cane during cane gait training due to technical problems. Additionally, it is difficult for patients to receive accurate feedback on weight support on the paretic lower limb during cane gait training [ 23 ]. Moreover, there is insufficient information on the effects of progressive weight support induction on the affected lower limb during cane gait training on muscle activity and gait in patients with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…It has demonstrated significant efficacy in defending against diarrhoea caused by Escherichia coli and can serve as a prophylactic measure against ETEC infection. [36] Bromelain has also been documented to possess anti-helminthic activity against gastrointestinal nematodes such as Trichuris muris and Trichoderma viride. [37] This implies that it can counteract various effects associated with intestinal pathogens.…”
Section: Pharmacological Properties and Health Benefits Of Pineapple ...mentioning
confidence: 99%